2019
DOI: 10.1121/1.5078605
|View full text |Cite
|
Sign up to set email alerts
|

Partial devoicing of voiced geminate stops in Tokyo Japanese

Abstract: Tokyo Japanese has a constraint against voiced geminate stops in its native lexicon. The present study investigates whether recently introduced word-medial voiced geminate stops [C1V1C(C)2V2] are differentiated from voiceless geminates and voiced singletons in terms of duration, voicing during closure, and spectral moments of stop release bursts. The findings suggest that the voiceless and voiced singleton stops were clearly differentiated by C2 duration. In contrast, C2 duration of the voiceless and voiced ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 49 publications
1
3
0
Order By: Relevance
“…The result of the rt-MRI supports our previous acoustical analysis with five speakers of the Ikema dialect (including the two analyzed in this paper), showing that word-medial geminate consonants and word-initial geminate fricatives are significantly longer than their singleton counterparts (Shinohara & Fujimoto 2018). The clear length difference conforms to word-medial geminates in standard Japanese (Han 1962(Han , 1994Homma 1981;Beckman 1982;Idemaru &Guion 2008 andHussain &Shinohara 2019 among others) and other languages that have a singleton-geminate contrast (e.g. Ham 2001, Ridouane 2007, Hussain 2015.…”
Section: Articulatory Duration and Strengthsupporting
confidence: 55%
See 1 more Smart Citation
“…The result of the rt-MRI supports our previous acoustical analysis with five speakers of the Ikema dialect (including the two analyzed in this paper), showing that word-medial geminate consonants and word-initial geminate fricatives are significantly longer than their singleton counterparts (Shinohara & Fujimoto 2018). The clear length difference conforms to word-medial geminates in standard Japanese (Han 1962(Han , 1994Homma 1981;Beckman 1982;Idemaru &Guion 2008 andHussain &Shinohara 2019 among others) and other languages that have a singleton-geminate contrast (e.g. Ham 2001, Ridouane 2007, Hussain 2015.…”
Section: Articulatory Duration and Strengthsupporting
confidence: 55%
“…In standard Japanese, voiced obstruent geminates are observed only in recent borrowings such as /beddo/ 'bed' or /baggu/ 'bag' and in onomatopoeia. Acoustic analyses clearly indicated that those voiced geminates are partially or fully devoiced (Kawahara 2006, Matsuura 2012, Fujimoto & Funatsu 2018, Hussain & Shinohara 2019. However, acoustic analyses of voiced geminates in the dialects of the Kumamoto and Amakusa areas of Kyushu, Japan, showed that the amount of voicing during the closure phase varied, depending on words, speakers, sub-dialects, and tokens, indicating the instability of voiced geminates in those dialects (Matsuura 2016, Takada 2018.…”
Section: Introductionmentioning
confidence: 99%
“…In Japanese, voiced geminates are disfavoured and their occurrence is limited mostly to loanwords (e.g. Hussein and Shinohara, 2019; Kawahara, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…Italian uses length contrasts for a wide variety of phonemes differing in voicing, place and manner of articulation [5,[12][13][14][15]. In Japanese, on the other hand, voiced geminates are disfavoured and their occurrence is limited mostly to loanwords [16,17]. To record the stimuli to be used in the perception study, each word was presented on a computer screen in random order and was produced in two separate conditions: one in isolation and the other in a carrier sentence (/diko X di nwɔvo/ 'I say X again' for Italian and /sokowa X to jomimasu/ 'You read it as X there' for Japanese).…”
Section: Speakersmentioning
confidence: 99%